A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Bittig, Henry C.; Maurer, Tanya L.; Plant, Joshua N.; Schmechtig, Catherine; Wong, Annie P. S.; Claustre, Hervé; Trull, Thomas W.; Udaya Bhaskar, T. V. S.; Boss, Emmanuel; Dall’Olmo, Giorgio; Organelli, Emanuele; Poteau, Antoine; et al. (Frontiers in Marine Science, 2019)
The Biogeochemical-Argo program (BGC-Argo) is a new profiling-float-based, ocean wide, and distributed ocean monitoring program which is tightly linked to, and has benefited significantly from, the Argo program. The community has recommended for BGC-Argo the addition of six measurements in addition to pressure, temperature and salinity measured by Argo, to include oxygen, pH, nitrate, downwelling light, chlorophyll fluorescence and the optical backscattering coefficient. The purpose of this addition is to enable the monitoring of ocean biogeochemistry and health, and in particular, monitor major processes such as ocean deoxygenation, acidification and warming and their effect on phytoplankton, the main source of energy of marine ecosystems. Here we describe the salient issues associated with the operation of the BGC-Argo network, with information useful for those interested in deploying and using the data it produces. These include, float testing, deployment and increasingly, recovery. Aspect of data management, processing and quality control are covered as well as specific issues associated with each of the six BGC-Argo sensors. In particular, it is recommended that water samples be collected during float deployment to be used for validation of sensor output.